Perceptual chunking and its effect on memory in speech processing: ERP and behavioral evidence - Gilbert, Annie C.; Boucher, Victor J.; Jemel, Boutheina (Frontiers in Psychology, 2014)
We examined how perceptual chunks of varying size in utterances can influence immediate memory of heard items (monosyllabic words). Using behavioral measures and ERPs (N400) we evaluated the quality of the memory trace for targets taken from perceived temporal groups of 3 and 4 items. Variations in the amplitude of the N400 showed a better memory trace for items presented in temporal groups of 3 compared to those in groups of 4. Analyses of behavioral responses along with P300 components also revealed effects of chunk position in the utterance. This is the first study to measure the on-line effects of perceptual chunks on the memory trace of spoken items. Taken together, the N400 and P300 responses demonstrate that the perceptual chunking of speech facilitates information buffering and a processing on a chunk-by-chunk basis.